If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(6x + 12) = 1.6 + -1(x + 2) Reorder the terms: 0.6(12 + 6x) = 1.6 + -1(x + 2) (12 * 0.6 + 6x * 0.6) = 1.6 + -1(x + 2) (7.2 + 3.6x) = 1.6 + -1(x + 2) Reorder the terms: 7.2 + 3.6x = 1.6 + -1(2 + x) 7.2 + 3.6x = 1.6 + (2 * -1 + x * -1) 7.2 + 3.6x = 1.6 + (-2 + -1x) Combine like terms: 1.6 + -2 = -0.4 7.2 + 3.6x = -0.4 + -1x Solving 7.2 + 3.6x = -0.4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7.2 + 3.6x + x = -0.4 + -1x + x Combine like terms: 3.6x + x = 4.6x 7.2 + 4.6x = -0.4 + -1x + x Combine like terms: -1x + x = 0 7.2 + 4.6x = -0.4 + 0 7.2 + 4.6x = -0.4 Add '-7.2' to each side of the equation. 7.2 + -7.2 + 4.6x = -0.4 + -7.2 Combine like terms: 7.2 + -7.2 = 0.0 0.0 + 4.6x = -0.4 + -7.2 4.6x = -0.4 + -7.2 Combine like terms: -0.4 + -7.2 = -7.6 4.6x = -7.6 Divide each side by '4.6'. x = -1.652173913 Simplifying x = -1.652173913
| 4/5=-4g/7 | | 3x+13+5x-7= | | -3(2+5a)-10=22+6a | | 11/10(7/3) | | 8(4y-8)=12 | | (5x^2+7)-(-4y^2+7)= | | lr-3l=15 | | (1/2+3/5) | | 24-6j=36 | | 0.6(x+12)=1.6-(x+2) | | -1d/6=-4 | | 2y+1=3y+5 | | 1.6e-0.5=7.5 | | (1/2+3/5)/3/7 | | -7(5x-9)=27-4x | | 2/3x+7=28 | | 6x-(5x+4)=5x-24 | | x^2-10x+23= | | z-29=-35 | | -5n+14=-4n-16 | | -1(6x-2y)=-1(50) | | 4X+1/3=11 | | -2-2/3-3/5 | | x=0-4(7)(-3) | | 3/5(d/8+1/4)=9/16 | | 2x-13x(4-1)=-46 | | 3/8-1/2(3/4)^2 | | p=a+b-3 | | 10x+20=14x | | 2x-3x(4-x)=-46 | | 1/2(5/6)^2+2/9 | | 4y-3(y-4)+4=7 |